Effectiveness of the "CEPAT" (Smart and Compliant) Health Promotion Model on Blood Pressure Control in Hypertensive Patients: A Quasi-Experimental Study - Dewi Hartinah; Ika Tristanti; Iswatun Qasanah (Journal of Public Health Sciences, 2026)
The necessity for efficient non-pharmacological methods to supplement medical therapy is highlighted by the fact that hypertension remains a major global public health concern. In Kudus Regency, Indonesia, this study looked at how well the CEPAT health promotion model worked to lower blood pressure in hypertensive individuals. Purposive sampling was used to choose 32 individuals from PRM 02 Pasuruhan Lor for a quasi-experimental study with a pre-test–post-test control group design. Participants were split equally between a control group (n = 16) and an intervention group. While the control group got standard care, the intervention group participated in a four-week CEPAT health promotion program. Following the intervention, the diastolic blood pressure decreased from 103.71 ± 1.03 mmHg to 93.13 ± 0.93 mmHg (p = 0.001) and the systolic blood pressure decreased significantly from 167.81 ± 32.19 mmHg to 135.63 ± 16.43 mmHg (p < 0.001). On the other hand, the control group showed no statistically significant changes. A substantial difference between the two groups was also shown by post-intervention analysis (p < 0.001). These results imply that the CEPAT health promotion model is a useful community-based intervention for improving blood pressure control and could be a useful tactic for managing hypertension.